До 200-річчя від дня народження Федора Достоєвського (1821–1881) - Dzyk, Roman (Yuriy Fedkovych Chernivtsi National University, 2021)
To the 200th Anniversary of Fyodor Dostoevsky
To the 200th Anniversary of Fyodor Dostoevsky
Keywords: Fyodor Dostoevsky; Anniversary; Bibliography